Psychology of motivation [soundrecording] - Waitley, Denis (New York Simon & Schuster Audios, 1993)
Presents the six types of achievement motivations. Gives a clear-cut map to plot your course toward the achievements you want, identify the pitfalls caused by fear and competitiveness, incease feelings of inner power and effectiveness and develop the persistence to accomplish whatever is desired through improved time-control methods.
An abridgement of Denis Waitley's Psychology of human motivation.
Keywords: Motivation (Psychology); Personality and motivation; Psychology